Pattern of Response to Bronchial Challenge with Histamine in Patients with Non-Atopic Cough-Variant and Classic Asthma - Vladimir Zugic (Journal of Clinical Medicine, 2018)
Background: The aim of this study was to establish whether non-atopic patients with cough variant asthma (CVA) have different pattern of response to direct bronchoconstrictors than non-atopic patients with classic asthma (CA). Method: A total of 170 patients of both sexes with stable CVA and CA were screened for the study and 153 were included. Patients with proven atopy were not included and 17 patients with worsening of their condition or with verified bronchial obstruction during screening were excluded. All included patients performed spirometry and underwent a bronchial challenge with histamine according to long-standing protocol in our laboratory. Results: Significantly higher frequency of bronchial hyper-responsiveness (BHR) was found in patients with CA than in patients with CVA (63.9% vs. 44.9%, respectively; p < 0.05). Sensitivity was significantly lower in patients with CVA (p < 0.05), while no significant difference was found in maximal response and responsiveness. Only patients with positive challenge tests were included in the analysis. Conclusion: Adult non-atopic patients with CVA and CA have a pattern of response to non-specific bronchial stimuli similar to atopic patients with same conditions, with the exception of similar maximal response, which may reflect the efficacy of previous treatment. We believe that further studies are needed to clarify the mechanisms involved in airway response to non-specific stimuli in CVA and CA, especially in non-atopic patients. Further studies should also clarify whether this response pattern has any implications on clinical presentation or on treatment options.